PENGARUH LATIHAN MEROBOHKAN CONE LAWAN TERHADAP AKURASI PASSING DALAM PERMAINAN SEPAK BOLA SSB PORSIL - Deddy Rahmat Saputra (Jurnal Muara Olahraga, 2021)
Abstract The problem in this research is the lack of passing accuracy in the SSB Porsil soccer game. This study aims to see the effect of the practice of knocking down the cone on the accuracy of passing in a soccer game. This research is an experimental research. The population in this study were all students of SSB Porsil who were still active in participating in the training and amounted to 47 people. The sample in this study was the age of 10-12 years as many as 20 people. The sampling technique was carried out by purposive sampling technique. The instrument in this study is a short pass test to measure passing accuracy. The data analysis technique used the Lilliefors normality test and t-test with a significant level of = 0.05. The result of the research is that there is an effect of knocking down the opponent's cone on the accuracy of passing in the SSB Porsil football game. This is proven significantly, where after the "t" test the results obtained are tcount (1.77) > ttable (1.72), Ho is rejected while Ha is accepted. Based on the results of the study, it can be concluded that there is a significant effect of knocking down the opponent's cone on the accuracy of passing in the SSB Porsil soccer game. Keywords: Cone, Accuracy, Passing, Pratice